Introduction to the Early Childhood Issue - Forstadt, Leslie; Peavey, Sheryl (Maine Policy Review, 2009)
Guest editors Leslie Forstadt and Sheryl Peavey introduce the articles in this special issue of Maine Policy Review on early childhood by highlighting the myriad of programs and policies affecting Maine’s young children and their families. To illustrate the challenges faced by parents, they present the fictional account of a young woman facing an unexpected pregnancy. The story illustrates the sometimes confusing array of services, programs, and funding for young children and their parents. The authors argue “it is time to make every door into the system of early childhood services the right door for every parent.”